The Impact of Antioxidants in Blood Pressure and Free Radicals of Athletes - Mohammed Nader Shalaby; Sherin Hussien; Mona Mostafa Abdo Sakoury; Adel Mohamed Mohamed Atiaa; Mohamed Abdalla Antar Galila (Indian Journal of Forensic Medicine & Toxicology, 2021)
Many reports have defined oxidative stress as an imbalance between an enhanced reactive oxygen/nitrogenspecies and the lack of protective ability in antioxidants. From that point of view, free radical-induceddamage caused by oxidative stress seems to be a probable contributing factor to the pathogenesis of manynewborn diseases, such as respiratory distress syndrome, bronchopulmonary dysplasia, periventricularleukomalacia, necrotizing enterocolitis, patent ductus arteriosus, and retinopathy of prematurity. This studywas conducted on a sample of (30) players. researchers used the experimental approach (equivalent groupsfor its suitability and method of study. the sample was divided into two groups, (15) players representingthe control group and (15) players representing the experimental group. the study aims to identify theeffect of antioxidants on oxygenated blood pressure and free radicals for athletes. the study showed thatthere is an effect of antioxidants (vitamins on increasing the activity of the enzyme (SGOT) involved inATP rebuilding processes, and an effect of antioxidants on reducing oxygen blood pressure while not theeffect of antioxidants on SGPT enzyme activity is clear, which shows that it is not involved in reducing freeradical, muscle fatigue and blood pressure. Hence, the researchers came out with a set of recommendations,including the need to pay attention to taking vitamins because of their role in reducing the effects of freeradicals and emphasizing the gradual increase in training loads.